Acylcoenzyme A dehydrogenase deficiency in heart tissue from infants who died unexpectedly with fatty change in the liver. Issue 6614 (2nd January 1988) - Allison, Fiona; Bennett, M J; Variend, S; Engel, P C
Abstract : Heart muscle from infants who died unexpectedly and who showed fatty changes in the liver at necropsy was analysed for long chain and medium chain acylcoenzyme A dehydrogenase activities by using the natural electron acceptor. In two of the seven cases investigated a deficiency in acylcoenzyme A dehydrogenase activity was found. In one case the deficiency was in medium chain acylcoenzyme A dehydrogenase activity and in the other long chain acylcoenzyme A dehydrogenase activity. These findings emphasise the importance of investigating fatty acid oxidation in infants who have died unexpectedly.